An investigation on the safety of children on the roads of Gaza, Palestine - Yahya R Sarraj; Basma Bashbash (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
The traffic safety system in Palestine needs major improvements. Traffic accident data in Gaza Strip are collected from crash reports recorded by the local Police. In many cases, roads are constructed without proper consideration of children's needs. However, children and young kids use the roads as pedestrians, bicyclists, and occupants of vehicles. Moreover, they might choose to play on the road. This paper aims to investigate the situation of traffic safety of children in the Gaza Strip and to recommend measures to reduce their risk. This research is based on accident statistics recorded in the period between 2008 and 2018. Analysis was carried out to determine critical locations that have a high number of accidents, focusing on accidents that resulted in casualties and fatalities of children. Results show that the highest rate of children fatalities in the Gaza Strip was on Arterial Roads.  According to the data collected in 2016, 2017, and 2018, the percentage of road traffic deaths of children are 60%, 68% and 59% respectively, which is higher than the average rate of child mortality in the world (52%) according to the world organization statistics. Gaza city has the largest number of children fatalities caused by road accidents in the Gaza Strip. This might be due to the high population density and heavy traffic.  In order to reduce road accidents for children, it is necessary to control the speed of vehicles at school zones and to provide more safety measures for children on the roads, including illuminated pedestrian crossings for children. It is very important to provide children at schools and kindergartens with proper training on how to cross the street. It is also helpful to teach them some important traffic signs.